Making System Configuration More Declarative - DeTreville, Jon (Proceedings of the Tenth Workshop on Hot Topics in Operating Systems, 2005)
System administration can be difficult and painstaking work, yet individual users must typically administer their own personal systems. These personal systems are therefore likely to be misconfigured, undependable, brittle, and insecure, which restricts their wider adoption. Because updating the configuration of today’s systems involve imperative updates in place, a system’s correctness ultimately depends on the correctness of every install and uninstall it has ever performed; because these updates are local in scope, there is no easy way to specify or check desired properties for the whole system. We present a more checkable declarative approach to system configuration that should improve system integrity and make systems more dependable. As in the earlier Vesta system, we define a system model as a function that we can apply to a collection of system parameters to produce a statically typed, fully configured system instance; models can reference and thereby incorporate submodels, including submodels exported by each program in the system. We further check each system instance against established system policies that can express a variety of additional ad hoc rules defining which system instances are acceptable. Some system policies are expressible using additional type rules, while others must operate outside the type system. A preliminary design and implementation of this approach are under way for the Singularity OS, and we hope to specify and check a number of ad hoc system properties for Singularity-based personal systems.